The protective role of jervine against radiation-induced gastrointestinal toxicity - Selvinaz Yakan; Tuba Aydin; Canan Gulmez; Ozkan Ozden; Kivilcim Eren Erdogan; Yusuf Kenan Daglioglu; Fundagul Andic; Onur Atakisi; Ahmet Cakir (Taylor & Francis Group, 2019)
In this study, we investigated whether jervine (J) could prevent gastrointestinal (GI) side effects of abdominopelvic radiotherapy (RT) in Wistar-Albino female rats. Rats were divided into five groups: control (C), J only (J), J administered at 5 mg/kg/days for 7 days, RT only (RT), J before RT (J + RT), J administered for seven days before RT, J both before and after RT (J + RT + J), and J administered for 7 days before RT and after RT for 3 days. The weights of rats were measured on the 1st, 7th, and 10th days of the study. Rats were sacrificed to obtain tissues from the liver and intestine, which was followed by taking blood samples intracardially. In addition, the tissues were stained with pyruvate dehydrogenase (PDH) immunohistochemically. In our study, J supplementation markedly reduced weight loss, and histopathological, immunohistochemical, biochemical results suggest that J had a protective effect on GI toxicity following RT.